Von der ''klassischen'' Verkehrs- zur zeitgemäßen Mobilitätserziehung. - Flade, Antje; Hacke, Ulrike (Deutscher Verkehrs-Verlag, 2004)
Das Leitbild einer an Nachhaltigkeit orientierten Entwicklung fordert eine reflektierte Verkehrsmittelwahl. Doch wie wird dieser Anspruch den heutigen Kindern und Jugendlichen vermittelt? Am Beispiel einer neu entwickelten Lernsoftware für die Klassenstufen 5 bis 7 werden Möglichkeiten aufgezeigt, wie mit Hilfe zeitgemäßer Erziehung die Herausbildung eines kritischen Mobilitätsbewusstseins gefördert und der Manifestierung einer autoorientierten Haltung vorgebeugt werden kann. difu

While the 'classic' approach to education in transport matters tended to focus on the ability to adapt to existing traffic conditions, the contemporary approach deals with present day mobility and eventual traffic structure changes. Children and young persons are - in future - no longer going to be trained to participate in traffic proficiently and according to existing rules. Instead, they are to appreciate traffic as a socio-societal product and to learn a new approach towards shared responsibility. To support this learning process, educational aid is needed that will motivate children and young persons to deal with the topic in line with their experiences. Suitable Internet-based educational material for cyclists is at hand for classes 5 to 7. The intention is to firm up the known positive attitude towards cycling - as found within this age group - and to redirect the approach to mobility from one-sided focus on car usage to a more open-minded attitude towards future means of transport. difu
Keywords: Verkehr; Verkehrsmittelwahl; Individualverkehr; Fahrrad; Kind; Lernen; EDV-Software; Verkehrsteilnehmer; Verkehrserziehung; Mobilitätsverhalten; Orientierung; Fahrradbenutzung; Fahrradverkehrsförderung